Educating Early Childhood Prayer Procedures Through ChatGPT-Based Interactive Media with Studio Ghibli Style Visuals - Jufri, Jufri; Djalia, La Ode Sahrin; Ramadhan, Arfan Fadil; Khatimah, Nurul (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
Early childhood Islamic education plays a strategic role in shaping spiritual, moral, and social character. One essential aspect is teaching prayer procedures, which not only fulfill religious obligations but also instill values such as discipline, cleanliness, and focus. However, conventional teaching methods are often ineffective for young learners who require visual, auditory, and kinesthetic engagement. This community service initiative aimed to develop an innovative learning media combining ChatGPT-based interactivity with Studio Ghibli-inspired visual design to enhance children's understanding of prayer. The method involved four stages: problem analysis, media development, and implementation. The program was conducted at TK IT Rumah Anak Saleh in Buton and involved active participation from early childhood educators. The resulting media featured AI-driven natural language interactions and visually engaging illustrations created via ChatGPT and designed with Canva. Implementation involved guided learning sessions using visual posters and multisensory approaches to teach prayer movements and recitations. The results showed high enthusiasm and engagement among children, improved understanding of prayer, and effective memorization through enjoyable learning experiences. In conclusion, integrating AI technology and imaginative visuals proved effective in delivering Islamic education to young children and offers a promising model for enhancing spiritual literacy in the digital era.